2009
DOI: 10.1155/2009/839308
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Iron Overload: Lessons from the HEmochromatosis and IRon Overload Screening (HEIRS) Study

Abstract: Generalized population screening in a primary care population as performed in the HEIRS Study is not recommended. There may be a role for focused screening in Caucasian men, with some debate regarding genotyping followed by phenotyping, or phenotyping followed by genotyping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…Likewise, in the general population from which the patients with diabetes in this study were identified, the positive and negative predictive values of TS $50% for detecting C282Y/C282Y were 12% and 99%, respectively; and the sensitivity and specificity were 70% and 99%, respectively. Thus, the specificities were comparable and high, and corresponded to those reported in The Hemochromatosis and Iron Overload Screening Study (HEIRS) (40). The sensitivity was highest among patients with late-onset type 1 diabetes; but in the general population overall and in patients with type 2 diabetes, sensitivities corresponded to those in HEIRS but were relatively low, limiting the role of TS as a screening test.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Likewise, in the general population from which the patients with diabetes in this study were identified, the positive and negative predictive values of TS $50% for detecting C282Y/C282Y were 12% and 99%, respectively; and the sensitivity and specificity were 70% and 99%, respectively. Thus, the specificities were comparable and high, and corresponded to those reported in The Hemochromatosis and Iron Overload Screening Study (HEIRS) (40). The sensitivity was highest among patients with late-onset type 1 diabetes; but in the general population overall and in patients with type 2 diabetes, sensitivities corresponded to those in HEIRS but were relatively low, limiting the role of TS as a screening test.…”
Section: Discussionsupporting
confidence: 67%
“…Two recent articles (40,41) have reviewed the principles of screening according to the World Health Organization guidelines in the context of hereditary hemochromatosis and conclude that generalized population screening in primary care is generally not recommended; however, there may be a role for focused screening in Caucasian men (40) because 84% of men .55 years of age have elevated ferritin levels and 37% have ferritin levels .1,000 mg/L, which is a generally accepted threshold for organ impairment (41). The reasons for the conclusions, among others, are that the gold standard measure for the screening has not yet been clarified (TS, ferritin, or both, and/or genetic screening?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…81 First, although genetic testing is well accepted and associated with a minimal risk of discrimination, generalized population screening in a primary care population as performed in the HEIRS Study is not recommended. Elevations of serum ferritin are common, particularly in Asians, Pacific Islanders, and African Americans.…”
Section: Discussionmentioning
confidence: 99%
“…The subsequent study, the Hemochromatosis and Iron Overload Screening (HEIRS) study, evaluated 20,000 multi-ethnic primary care-based adults from our institution [2]. Both studies provided insight on the prevalence and clinical relevance of HFE gene mutations, and the feasibility of and optimum approach to widespread screening for HH [3]. The objective of this study was to determine whether these studies had an effect on screening for HFE gene mutations on non-study populations residing in our community.…”
Section: Introductionmentioning
confidence: 99%